A escola nova e a modernização do ensino primário na Paraíba: a formação de professores e os grupos escolares (1930-1946) - Freire, Evelyanne Nathaly Cavalcanti de Luna (2016)
This thesis aims to present issues related to the history of school education and the educational politics of Paraíba in the period of 1930 to 1946 marked by great effervescence social politics and, especially in the educational field. The documentary research was conducted at the Historical Archive of Paraíba State Waldemar Bispo Duarte, linked to the Cultural Foundation – FUNESC, and in the Historical and Geographic of Paraíba – IHGP and in the Archdiocese of Paraíba Ecclesiastical Archives, more specifically referring to the news published in the Union Newspaper and in the Newspaper the Press. It was used as a source, copies of the Education Magazine, besides the rules, laws, decrees and national and local executive laws related both primary education and normal education as those relating to the organization of school education in its broadest sense. Thus, this study aims to discuss the primary school education of Paraíba, trying to emphasize aspects of modernization of education by the movement of the New School and punctuated by the process of expanding school groups. Therefore, we have tried to observe how the primary school of Paraiba was structured, considering permanently the relationship between the national guidelines and local specificities. We performed the analysis by trying to maintain a dialogue of the sources collected with a critical reading of the historical production for the period studied. The reflection was based on the theoretical framework advocated by Hobsbawm (2013), which points us about changes and innovations that have occurred, as well as watching some aspects that tended to remain, both locally and national. We also appropriated of some theoretical directions proposed by Thompson (2001), especially the ideas related to the political and cultural peculiarities, as those woven by Gramsci (1992) in relation to the correlation of political and social forces. In order to refer to the issues more directly related to the education, we approached the written hired by Saviani (2011), seeking to realize the movement of issues relating to pedagogical ideas during the stated period. This way the theoretical frameworks subsidized us to understand how the primary education was thought, designed and structured. We were also concerned in observing the most general terms of the process of formation or qualification of the teachers that worked in the primary education. We have considered that many were political and educational clashes between liberals and catholics, as well as the strong presence of the ideals of the new school throughout the period studied, which presented us with a broad and tense historical setting of Paraiba and national.